2014
DOI: 10.1089/ped.2014.0333
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Five Types of House Dust Mite in a Group of Allergic Egyptian Children

Abstract: Background: The published data on house dust mite (HDM) sensitization from Egypt are scanty. We sought to investigate the sensitization to five different types of HDM among a group of allergic children in a trial to outline the most frequent sensitizing strains in the Cairo Province. Methods: We consecutively enrolled 100 asthmatic patients, aged 1-7 years, of whom 22 had concomitant skin allergy. Skin prick testing was performed using allergen extracts of Dermatophagoides pteronyssinus, Dermatophagoides farin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
(14 reference statements)
1
11
0
1
Order By: Relevance
“…In the same city, the Odds ratios (95 % CI) for sensitization of a group of adolescents to D. pteronyssinus, D. farinae and B. tropicalis in relation with asthma were 7.28 (3.75–14.15), 2.65 (1.27–5.45) and 3.23 (1.68–6.21), respectively [ 263 ]. Sensitization to one or more mite species was reported in 24 % of Cairene children with allergic diseases; D. pteronyssinus and D. farinae were the most common sensitizers [ 264 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same city, the Odds ratios (95 % CI) for sensitization of a group of adolescents to D. pteronyssinus, D. farinae and B. tropicalis in relation with asthma were 7.28 (3.75–14.15), 2.65 (1.27–5.45) and 3.23 (1.68–6.21), respectively [ 263 ]. Sensitization to one or more mite species was reported in 24 % of Cairene children with allergic diseases; D. pteronyssinus and D. farinae were the most common sensitizers [ 264 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 This study found that patients with persistent asthma used to have a sensitization to at least 3 of the mites studied. Puerta et al 12 found that among 77 patients with asthma and/or rhinitis positive to Der f or Der p, over 70 % had sensitization to other mites (Der f 89 %, Ale o 68 % Blo t 80 %, Der p 75 % Cho 71 %, Lep d 59 %), indicating that sensitization in Cartagena is common to Pyroglyphidae mites (Der f, Der p) and mites from other families.…”
Section: Introductionmentioning
confidence: 82%
“…Studies have shown that the most common inhalant allergens are Dermatophagoides farinae, D. pteronyssinus, cats, and dogs (13). D. pteronyssinus and D. farinae also represent the most common sensitizing strains of house dust mites (16).…”
Section: Discussionmentioning
confidence: 99%